Clinical predictors for bradycardia and supraventricular tachycardia necessitating therapy in patients with unexplained syncope monitored by insertable cardiac monitor. Issue 5 (16th March 2021) - Onuki, Tatsuya; Shoji, Makoto; Sugiyama, Hiroto; Arai, Shuhei; Yoshikawa, Kosuke; Mase, Hiroshi; Kurata, Masaaki; Kikuchi, Miwa; Wakatsuki, Daisuke; Asano, Taku; Suzuki, Hiroshi; Tanno, Kaoru; et al.
Abstract: Background: Insertable cardiac monitors (ICMs) improve diagnostic yield in patients with unexplained syncope. The most of cardiac syncope is arrhythmic causes include paroxysmal bradycardia and supraventricular tachycardia (SVT) in patients with unexplained syncope receiving ICM. Predictors for bradycardia and SVT that necessitate therapy in patients with unexplained syncope are not well known. Hypothesis: This study aimed to investigate predictors of bradycardia and SVT necessitating therapy in patients with unexplained syncope receiving ICMs. Methods: We retrospectively reviewed medical records of consecutive patients who received ICMs to monitor unexplained syncope. We performed Cox's stepwise logistic regression analysis to identify significant independent predictors for bradycardia and SVT. Results: One hundred thirty‐two patients received ICMs to monitor unexplained syncope. During the 17‐month follow‐up period, 19 patients (14%) needed pacemaker therapy for bradycardia; 8 patients (6%) received catheter ablation for SVT. The total estimated diagnostic rates were 34% and 48% at 1 and 2 years, respectively. Stepwise logistic regression analysis indicated that syncope during effort (odds ratio [OR] = 3.41; 95% confidence interval [CI], 1.21 to 9.6; p  = .02) was an independent predictor for bradycardia. Palpitation before syncope (OR = 9.46; 95% CI, 1.78 to 50.10; p  = .008) and history of atrial fibrillation (OR = 10.1; 95% CI, 1.96 to 52.45; p  = .006) were identified as significant independent predictors for SVT. Conclusion: Syncope during effort, and palpitations or history of atrial fibrillation were independent predictors for bradycardia and for SVT. ICMs are useful devices for diagnosing unexplained syncope.